Standardization of the Korean Version of the Geriatric Depression Scale: Reliability, Validity, and Factor Structure - Kim, Ji Yang (Korean Neuropsychiatric Association, 2008)
OBJECTIVE: We developed a Revised Korean version of the Geriatric Depression Scale (GDS-KR) and examined its reliability, validity, and factor structures. We also estimated its optimal cutoff scores for major depressive disorder (MDD) and minor depressive disorder (MnDD) stratified by age and education. METHODS: The GDS-KR was administered to 888 subjects (61 MDD patients, 45 MnDD patients, and 782 normal elders). Its internal consistency and test-retest reliability were examined. Its concurrent validity was evaluated using Pearson correlation coefficients with the Korean version of the Center for Epidemiologic Studies Depression Scale (CES-D-K) and Hamilton Depression Rating Scale (HAM-D). The mean GDS-KR scores of the MDD patients, MnDD patients and normal elders were compared to evaluate its discriminant validity. To evaluate its construct validity, a principal component analysis with varimax rotation was performed. Receiver operator characteristic (ROC) curve analyses were performed to evaluate its diagnostic ability. RESULTS: Chronbach's coefficient alpha for the GDS-KR was 0.90 and the test-retest reliability was 0.91 (p<0.01). The Pearson correlation coefficients of the GDS-KR scores with the CES-D-K and HAM-D scores were 0.63 (p<0.01) and 0.56 (p<0.01), respectively. The GDS-KR consisted of 5 factors. The optimal cut-off scores of the GDS-KR were 16/17 for MDD only and 15/16 for both MDD and MnDD. The optimal cutoff scores of the GDS-KR were higher in the less educated and younger subjects. The diagnostic accuracy for MDD of the GDS-KR was higher than that of the CES-D. CONCLUSION: The GDS-KR was found to be a reliable and valid questionnaire for screening MDD and MnDD in late life.